Analisis Kesulitan Belajar Siswa dalam Menyelesaikan Soal Cerita Pendek pada Mata Pelajaran Bahasa Indonesia di SD Inpres Tidung II - Farhi, Muh; Tarman, T; Latief, Syekh Adiwijaya (Wacana Akademika: Majalah Ilmiah Kependidikan, 2024)
This research aims to analyze students' difficulties in solving short story questions in Indonesian language subjects in class III UPT SPF SDN Inpres Tidung II. This research is qualitative research with a descriptive approach. The subjects in this research were 15 students consisting of five students with high, medium and five low abilities. Data collection was carried out by written tests and continued with interviews. The results of the analysis of students' learning difficulties in solving short story questions showed an average score of 56.47. From these data it is known that the level of ability of class III students is still low. Of the 5 questions given to students, there were still many who had difficulty answering questions related to moral messages and character traits. Based on the results of interviews with 15 students, it was discovered that there were no difficulties in the high subject category. The difficulty in the medium subject category is that it is difficult to determine the moral message and character traits. Meanwhile, the difficulty in the low subject category is that it is difficult to understand the questions given. Based on the results of the research that has been carried out, it can be concluded that there are still many students who experience difficulties in solving short story questions in Indonesian subjects.